The Affordable Care Act and the Growth of Involuntary Part-Time Employment - William E. Even; David A. Macpherson (Institute for the Study of Labor (IZA), 2015)
This study tests whether the employer mandate under the Affordable Care Act (ACA) increased involuntary part-time (IPT) employment. Using data from the Current Population Survey between 1994 and 2014, we find that IPT employment in 2014 was higher than predicted based on economic conditions and the composition of jobs and workers in the labor market. More importantly, using difference-in-difference methods, we find that the increase in the probability of IPT employment since 2010 was greatest in the industries and occupations where workers were most likely to be affected by the mandate. We also show that there has been virtually no change in the probability of IPT employment where the number of workers affected by the mandate was small. We estimate that approximately 1 million additional workers between the ages of 19 and 64 are in IPT employment as a result of the ACA employer mandate.
Keywords: J22; J23; J32; J33; H25; 330; Affordable Care Act; involuntary part-time employment; employer mandate; health insurance